A General Overview to Public Library Services in Germany from the Point of Turkish Immigrants - Gülcan Palo (Türk Kütüphaneciliği)
Turkish population in Germany effects social, political and economic development of Germany. Therefore different library services exist in German librarianship. In this study it is given the examples of services in five public libraries in Germany. Aim of the study is to present general consideration of library services from five public libraries in Germany which are important in the sense of cultural improvement of Turkish immigrants. In this context these libraries and their services is represent with the information obtained by observations and interview methods.